Preparation method of carbon / carbon surface ZrB2-MoSi2-ZrSi2 high oxygen barrier coating
The microcrystalline layer was generated through powder source microoxidation technology, which solved the problem of strong volatility of oxidation by-products in medium and low temperature environments, achieving pore healing and thermal stress relief in the coating, significantly improving dynamic oxidation resistance and structural stability.
Patent Information
- Application Number
- CN202510308753.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-17
- Publication Date
- 2025-06-17
AI Technical Summary
The existing ZrB2-MoSi2-ZrSi2 coating is prone to strong volatile oxidation by-products in medium and low temperature environments, resulting in a decrease in the stability of the composite glass layer and insufficient dynamic oxidation resistance.
The powder source micro-oxidation technology is used to perform micro-oxidation treatment through a high-temperature muffle furnace to generate an in-situ microcrystalline layer, which enhances the healing ability of loose holes inside the coating, and uses the microcrystalline layer as a thermal expansion diluent to alleviate the problem of thermal stress concentration.
It significantly improves the dynamic oxidation resistance of the coating, enhances the structural oxygen resistance performance, alleviates the problem of thermal expansion coefficient mismatch, and improves the stability and durability of the coating under extreme conditions.
Smart Images

Figure CN120157513A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coatings, and specifically to a preparation method of a high oxygen resistance coating of ZrB2-MoSi2-ZrSi2 on a carbon / carbon surface. Background Art
[0002] Carbon structural materials (including C / C composites and graphite) are considered to be a highly potential lightweight material due to their high melting point, high strength, low thermal expansion coefficient and other characteristics, and are widely used in the aerospace field. However, these materials will react with oxygen in an aerobic environment above 673K, resulting in the failure of the carbon matrix. So far, antioxidant coating technology is recognized as the most effective means to inhibit the oxidation of carbon materials.
[0003] As an excellent ultra-high temperature ceramic component, ZrB2 is regarded as a promising antioxidant material due to its excellent antioxidant performance and melting point as high as 3523K. However, since the oxidation protection process of the coating is actually a process in which its components are oxidized and consumed, the release of gaseous B2O3 generated by the oxidation of ZrB2 will form pores in the coating, thus significantly weakening the antioxidant ability of the ZrB2-SiC coating. In view of the vitrification ability of silicides being crucial to the antioxidant ability of the coating, in recent years, researchers have introduced transition metal silicides such as TaSi2, WSi2, ZrSi2 and MoSi2 into the ZrB2 coating to improve its antioxidant ability for carbon structural materials. Among these silicides, MoSi2 and ZrSi2 not only exhibit excellent glass-forming ability, but also are excellent sintering additives, which can significantly enhance the structural oxygen barrier of the coating. However, for the ZrB2-MoSi2-ZrSi2 coating, the oxidation by-products B2O3 and MoO3 have strong volatility in the medium and low temperature environment, and the volatilization of a large amount of gas will inevitably destroy the stability of the composite glass layer. Therefore, it is particularly necessary to improve the dynamic antioxidant ability of the ZrB2-MoSi2-ZrSi2 coating by constructing a high oxygen resistance coating structure in a wide temperature range.
[0004] Yang Yang et al. (Yang Yang. Research on the mechanical and antioxidant properties of ZrB2-20SiC ultra-high temperature ceramics modified by MoSi2 and TaSi2 [D]. University of Science and Technology of China, 2020) used MoSi2 to react with ZrB2 and B2O3 to generate a MoB solid phase, effectively reducing the volatile B2O3 and MoO3 phases, ensuring the integrity of the surface protective SiO2 layer, and thus significantly improving the ZrB2-20SiC ultra-high temperature ceramic at 5×10 3Antioxidant performance under air pressure of Pa and above. However, the high coefficient of thermal expansion of MoSi2 leads to an exacerbation of the thermal mismatch between the coating and the carbon matrix, and structural defects such as cracks are likely to occur. Yang Qingqing et al. (Yang Qingqing. Research on the Antioxidation Mechanism of MoSi2-HfB2-SiC Coatings [D]. China University of Mining and Technology, 2022) formed a high-quality Hf-B-Si-O sealing layer on the coating surface through pre-oxidation treatment, significantly improving the dynamic stability of the coating in an aerobic environment with relatively low losses. However, although pre-oxidation treatment can pre-generate a sealing glass layer on the coating surface, due to the difference in oxygen partial pressure inside and outside, the film-forming process on the coating surface has a certain timeliness, and it is difficult to provide timely healing for the loose pores inside the coating, which greatly inhibits the oxygen barrier effect of the coating structure; on the other hand, if the film-forming form of pre-oxidation is necessarily accompanied by the loss of coating components, this exacerbates the deterioration of the oxygen barrier of the structure to a certain extent, which is not conducive to the construction of a three-dimensional high oxygen barrier for the coating.
[0005] Therefore, a feasible method is urgently needed to solve the problem of the deterioration of the oxygen barrier performance caused by the insufficient oxygen barrier protection of the coating structure in the current technology. Summary of the Invention
[0006] The present invention aims to provide a method for preparing a high oxygen barrier coating of ZrB2-MoSi2-ZrSi2 on the surface of carbon / carbon, specifically a method for enhancing the oxygen barrier of the coating structure by using powder source micro-oxidation technology, so as to solve the drawbacks existing in the above-mentioned prior art.
[0007] A method for preparing a high oxygen barrier coating of ZrB2-MoSi2-ZrSi2 on the surface of carbon / carbon specifically includes the following steps:
[0008] 1) Powder loading: MoSi2-ZrSi2-ZrB2 powder prepared by combustion synthesis method, and the powder is ground and then loaded into a zirconia boat.
[0009] 2) Micro-oxidation treatment: Start the high-temperature muffle furnace. Wait for the furnace to stabilize to the target micro-oxidation temperature, open the furnace door and put in the zirconia boat loaded with the powder, and carry out powder source micro-oxidation treatment.
[0010] 3) Cooling and grinding: Wait until the micro-oxidation treatment time is reached, take out the boat, take out the powder after self-cooling, and grind it again to obtain the micro-oxidized MoSi2-ZrSi2-ZrB2 powder.
[0011] 4) Preparation of high oxygen barrier coating: Use the micro-oxidized MoSi2-ZrSi2-ZrB2 powder as the powder source, and prepare the MoSi2-ZrSi2-ZrB2 high oxygen barrier coating through low-temperature hot pressing sintering technology.
[0012] As a preferred solution, in the MoSi2-ZrSi2-ZrB2 powder prepared by the combustion synthesis method in step 1),
[0013] the volume ratio of MoSi2, ZrSi2, and ZrB2 is 9:1:1 to 9:5:1.
[0014] As a preferred solution, the micro-oxidation temperature in step 2) is 400 to 1000 °C.
[0015] As a preferred solution, the micro-oxidation treatment time in step 3) is 200 s to 350 s.
[0016] The advantages of the present invention compared with the prior art are as follows:
[0017] 1. Through the optimization of the coating powder source micro-oxidation technology, by using the in-situ microcrystalline layer generated by the micro-oxidation on the surface of the powder source, it is possible to achieve timely healing of the loose pores inside the coating, solve the technical problem of suppressing the internal structure loosening of the coating, and achieve the effect of enhancing the oxygen barrier of the coating structure.
[0018] 2. Using the microcrystalline layer generated by the micro-oxidation on the surface of the coating powder source as the internal thermal expansion diluent of the coating, it overcomes the problem of thermal expansion coefficient mismatch during the densification process of the traditional coating, and effectively alleviates the cracking phenomenon caused by thermal stress concentration during the film formation process of the coating.
[0019] 3. Through the micro-oxidation of the coating powder source surface, the coating can quickly respond and soften in a multi-scale temperature range, and form a dense glassy oxygen barrier layer without damage, fundamentally overcoming the structural destructive dynamic evolution defect caused by the film formation loss of the coating, and further improving the stability and durability of the coating under extreme conditions. Description of the Drawings
[0020] Figure 1 It is the process flow chart of the present invention.
[0021] Figure 2 It is the X-ray diffraction phase analysis result of the ZrB2-MoSi2-ZrSi2 high oxygen barrier coating obtained in Examples 1 to 4 of the present invention and the conventional ZrB2-MoSi2-ZrSi2 coating obtained in Comparative Example 1.
[0022] Figure 3 It is the scanning electron microscope surface morphology diagram of the ZrB2-MoSi2-ZrSi2 high oxygen barrier coating obtained in Example 1 of the present invention.
[0023] Figure 4 It is the scanning electron microscope surface morphology diagram of the ZrB2-MoSi2-ZrSi2 high oxygen barrier coating obtained in Example 2 of the present invention.
[0024] Figure 5SEM surface morphology diagram of the ZrB2-MoSi2-ZrSi2 high oxygen resistance coating obtained in Example 3 of the present invention.
[0025] Figure 6 SEM surface morphology diagram of the ZrB2-MoSi2-ZrSi2 high oxygen resistance coating obtained in Example 4 of the present invention.
[0026] Figure 7 SEM surface morphology diagram of the conventional ZrB2-MoSi2-ZrSi2 coating obtained in Comparative Example 1 of the present invention.
[0027] Figure 8 SEM cross-sectional morphology diagram of the ZrB2-MoSi2-ZrSi2 high oxygen resistance coating obtained in Example 1 of the present invention.
[0028] Figure 9 SEM cross-sectional morphology diagram of the ZrB2-MoSi2-ZrSi2 high oxygen resistance coating obtained in Example 2 of the present invention.
[0029] Figure 10 SEM cross-sectional morphology diagram of the ZrB2-MoSi2-ZrSi2 high oxygen resistance coating obtained in Example 3 of the present invention.
[0030] Figure 11 SEM cross-sectional morphology diagram of the ZrB2-MoSi2-ZrSi2 high oxygen resistance coating obtained in Example 4 of the present invention.
[0031] Figure 12 SEM cross-sectional morphology diagram of the conventional ZrB2-MoSi2-ZrSi2 coating obtained in Comparative Example 1 of the present invention.
[0032] Figure 13 SEM cross-sectional morphology diagram of the ZrB2-MoSi2-ZrSi2 high oxygen resistance coating obtained in Example 1 of the present invention after high temperature oxidation at 1700°C.
[0033] Figure 14 SEM cross-sectional morphology diagram of the ZrB2-MoSi2-ZrSi2 high oxygen resistance coating obtained in Example 2 of the present invention after high temperature oxidation at 1700°C.
[0034] Figure 15 SEM cross-sectional morphology diagram of the ZrB2-MoSi2-ZrSi2 high oxygen resistance coating obtained in Example 3 of the present invention after high temperature oxidation at 1700°C.
[0035] Figure 16 SEM cross-sectional morphology diagram of the ZrB2-MoSi2-ZrSi2 high oxygen resistance coating obtained in Example 4 of the present invention after high temperature oxidation at 1700°C.
[0036] Figure 17 SEM cross-sectional morphology diagram of the conventional ZrB2-MoSi2-ZrSi2 coating obtained in Comparative Example 1 of the present invention after high-temperature oxidation at 1700°C.
[0037] Figure 18 High-temperature oxidation weight gain curves at 1700°C of the ZrB2-MoSi2-ZrSi2 high oxygen barrier coatings obtained in Examples 1 to 4 of the present invention and the conventional ZrB2-MoSi2-ZrSi2 coating obtained in Comparative Example 1. Specific Embodiments
[0038] The technical solution of the present invention is not limited to the following specific embodiments listed, and also includes any reasonable combination between the specific embodiments.
[0039] Example 1:
[0040] The preparation method of the ZrB2-MoSi2-ZrSi2 high oxygen barrier coating on the carbon / carbon surface involved in this example is specifically carried out according to the following steps:
[0041] (1) Prepare MoSi2-ZrSi2-ZrB2 powder with a volume ratio of 9:1:1 by combustion synthesis method. After grinding, the powder is loaded into a zirconia ark.
[0042] (2) Start the high-temperature muffle furnace. Wait for the furnace to stabilize at a micro-oxidation temperature of 400°C. Open the furnace door and put in the zirconia ark loaded with the powder for micro-oxidation treatment of the powder source.
[0043] (3) After reaching the micro-oxidation treatment time of 200 s, take out the ark. After self-heating and cooling, take out the powder and grind it again to obtain the micro-oxidized MoSi2-ZrSi2-ZrB2 powder.
[0044] (4) Use the micro-oxidized MoSi2-ZrSi2-ZrB2 powder as the powder source and prepare the MoSi2-ZrSi2-ZrB2 high oxygen barrier coating by low-temperature hot pressing sintering technology.
[0045] The phase structure, surface micro-morphology, and cross-sectional micro-morphology of the MoSi2-ZrSi2-ZrB2 high oxygen barrier coating prepared in Example 1 are respectively as Figure 2 , Figure 3 , Figure 8 shown. The SEM cross-sectional morphology after high-temperature oxidation at 1700°C is as Figure 13 shown. The high-temperature oxidation weight gain curve at 1700°C is as Figure 18 shown.
[0046] Example 2:
[0047] The preparation method of the ZrB2-MoSi2-ZrSi2 high oxygen barrier coating on the carbon / carbon surface involved in this embodiment is specifically carried out according to the following steps:
[0048] (1) MoSi2-ZrSi2-ZrB2 powder with a volume ratio of 9:2:1 prepared by the combustion synthesis method is ground and then loaded into a zirconia ark;
[0049] (2) Start the high-temperature muffle furnace. Wait until the furnace is stable at a micro-oxidation temperature of 600 °C, open the furnace door, put in the zirconia ark loaded with the powder, and carry out micro-oxidation treatment of the powder source;
[0050] (3) After reaching the micro-oxidation treatment time of 250 s, take out the ark, take out the powder after self-heating and cooling, and grind it again to obtain the micro-oxidized MoSi2-ZrSi2-ZrB2 powder;
[0051] (4) Using the micro-oxidized MoSi2-ZrSi2-ZrB2 powder as the powder source, prepare the MoSi2-ZrSi2-ZrB2 high oxygen barrier coating by the low-temperature hot pressing sintering technology.
[0052] The phase structure, surface micro-morphology, and cross-section micro-morphology of the MoSi2-ZrSi2-ZrB2 high oxygen barrier coating prepared in Example 2 are respectively as shown in Figure 2 、 Figure 4 、 Figure 9 shown. The SEM cross-section morphology after high-temperature oxidation at 1700 °C is as shown in Figure 14 shown. The high-temperature oxidation weight gain curve at 1700 °C is as shown in Figure 18 shown.
[0053] Example 3:
[0054] The preparation method of the ZrB2-MoSi2-ZrSi2 high oxygen barrier coating on the carbon / carbon surface involved in this embodiment is specifically carried out according to the following steps:
[0055] (1) MoSi2-ZrSi2-ZrB2 powder with a volume ratio of 9:4:1 prepared by the combustion synthesis method is ground and then loaded into a zirconia ark;
[0056] (2) Start the high-temperature muffle furnace. Wait until the furnace is stable at a micro-oxidation temperature of 800 °C, open the furnace door, put in the zirconia ark loaded with the powder, and carry out micro-oxidation treatment of the powder source;
[0057] (3) After reaching the micro-oxidation treatment time of 300 s, take out the ark, take out the powder after self-heating and cooling, and grind it again to obtain the micro-oxidized MoSi2-ZrSi2-ZrB2 powder;
[0058] (4) Using the MoSi2-ZrSi2-ZrB2 powder treated by micro-oxidation as the powder source, a high-resistance oxygen barrier coating of MoSi2-ZrSi2-ZrB2 is prepared through low-temperature hot-pressing sintering technology.
[0059] In Example 3, the phase structure, surface micro-morphology, and cross-section micro-morphology of the prepared MoSi2-ZrSi2-ZrB2 high-resistance oxygen barrier coating are respectively as Figure 2 , Figure 5 , Figure 10 shown. The cross-section SEM morphology after high-temperature oxidation at 1700 °C is as Figure 15 shown, and the weight gain curve of high-temperature oxidation at 1700 °C is as Figure 18 shown.
[0060] Example 4:
[0061] The preparation method of the ZrB2-MoSi2-ZrSi2 high-resistance oxygen barrier coating on the carbon / carbon surface involved in this example is specifically carried out according to the following steps:
[0062] (1) Prepare MoSi2-ZrSi2-ZrB2 powder with a volume ratio of 9:5:1 by combustion synthesis method. After grinding the powder, load it into a zirconia ark.
[0063] (2) Start the high-temperature muffle furnace. Wait for the furnace to stabilize at the micro-oxidation temperature of 1000 °C, open the furnace door, put in the zirconia ark loaded with the powder, and carry out micro-oxidation treatment of the powder source.
[0064] (3) After reaching the micro-oxidation treatment time of 350 s, take out the ark, take out the powder after self-heating and cooling, and grind it again to obtain the MoSi2-ZrSi2-ZrB2 powder treated by micro-oxidation.
[0065] (4) Using the MoSi2-ZrSi2-ZrB2 powder treated by micro-oxidation as the powder source, a high-resistance oxygen barrier coating of MoSi2-ZrSi2-ZrB2 is prepared through low-temperature hot-pressing sintering technology.
[0066] In Example 4, the phase structure, surface micro-morphology, and cross-section micro-morphology of the prepared MoSi2-ZrSi2-ZrB2 high-resistance oxygen barrier coating are respectively as Figure 2 , Figure 6 , Figure 11 shown. The cross-section SEM morphology after high-temperature oxidation at 1700 °C is as Figure 16 shown, and the weight gain curve of high-temperature oxidation at 1700 °C is as Figure 18 shown.
[0067] Comparative Example 1:
[0068] The preparation method of the ZrB2-MoSi2-ZrSi2 coating on the carbon / carbon surface involved in this comparative example is a conventional preparation method of the ZrB2-MoSi2-ZrSi2 coating that does not utilize the powder source micro-oxidation technology, and specifically proceeds according to the following steps:
[0069] (1) MoSi2-ZrSi2-ZrB2 powder with a volume ratio of 9:4:1 prepared by the combustion synthesis method. After grinding, the powder is directly used as the powder source for coating densification;
[0070] (2) Using the MoSi2-ZrSi2-ZrB2 powder as the powder source, a conventional MoSi2-ZrSi2-ZrB2 coating is prepared by the low-temperature hot-pressing sintering technology.
[0071] The phase structure, surface microtopography, and cross-section microtopography of the conventional MoSi2-ZrSi2-ZrB2 coating prepared in Comparative Example 1 are respectively as shown in Figure 2 、 Figure 7 、 Figure 12 shown. The scanning electron microscope cross-section morphology after high-temperature oxidation at 1700°C is as shown in Figure 17 shown, and the high-temperature oxidation weight gain curve at 1700°C is as shown in Figure 18 shown. The process described in Comparative Example 1 is based on Example 3, removing steps (2) and (3), that is, without using the powder source micro-oxidation technology, and directly entering step (4). It can be found that the sample obtained in Comparative Example 1 has more defects after oxidation, providing a channel for oxygen diffusion. In addition, there is also a significant difference in the comprehensive oxygen barrier ability of the coating compared with the examples. Compared with Comparative Example 1, the oxidation weight gain of the samples with microcrystalline modification treatment (Examples 1-4) is significantly reduced, indicating a significant improvement in the oxygen barrier structure of the coating.
[0072] The present invention overcomes the problems in the prior art such as the difficulty in timely healing of the internal loose pores during the high-temperature oxygen barrier process of the coating, the deterioration of the structural oxygen barrier caused by film formation loss, and the structural defects caused by the difference in thermal expansion coefficient, and has the advantages of relieving the internal thermal stress of the coating, healing the internal loose pores of the coating, and enhancing the oxygen barrier of the coating structure.
[0073] The above describes the present invention and its implementation manners. This description is not restrictive. What is shown in the drawings is only one of the implementation manners of the present invention, and the actual structure is not limited thereto. Generally speaking, if those of ordinary skill in the art are inspired by it and design similar structural manners and embodiments without creative work without departing from the spirit of the present invention, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a carbon / carbon surface ZrB2-MoSi2-ZrSi2 high oxygen barrier coating, characterized in that: The specific steps include: 1) Powder loading: MoSi2-ZrSi2-ZrB2 powder prepared by combustion synthesis method is ground and loaded into zirconia ark; 2) Micro-oxidation treatment: start the high-temperature muffle furnace, wait until the furnace stabilizes to the target micro-oxidation temperature, open the furnace door and place the zirconium oxide ark filled with powder to perform powder source micro-oxidation treatment; 3) Cooling and grinding: When the micro-oxidation treatment time is reached, take out the ark, take out the powder after self-heat cooling, and grind it again to obtain MoSi2-ZrSi2-ZrB2 powder treated with micro-oxidation; 4) Preparation of high oxygen barrier coating: MoSi2-ZrSi2-ZrB2 high oxygen barrier coating was prepared by using slightly oxidized MoSi2-ZrSi2-ZrB2 powder as powder source through low temperature hot pressing sintering technology.
2. The method for preparing a carbon / carbon surface ZrB2-MoSi2-ZrSi2 high oxygen barrier coating according to claim 1, characterized in that: The volume ratio of MoSi2, ZrSi2 and ZrB2 in the MoSi2-ZrSi2-ZrB2 powder prepared by the combustion synthesis method in the step 1) is 9:1:1 to 9:5:
1.
3. The method for preparing a carbon / carbon surface ZrB2-MoSi2-ZrSi2 high oxygen barrier coating according to claim 1, characterized in that: The micro-oxidation temperature in step 2) is 400-1000°C.
4. The method for preparing a carbon / carbon surface ZrB2-MoSi2-ZrSi2 high oxygen barrier coating according to claim 1, characterized in that: The micro-oxidation treatment time in step 3) is 200s to 350s.
Citation Information
Patent Citations
Method for preparing SiO2-SiC mosaic structure microporous antioxidant coating on surface of carbon / carbon composite material
CN112142499A
Gradient oxygen barrier coating modified by utilizing rare earth doped binary boride and preparation method of gradient oxygen barrier coating
CN116239399A
Cold spraying method for high-content micro-oxidation-electronickelling coated silicon carbide particle reinforced aluminum-based composite coating
CN117305828A
Preparation method and application of multi-particle multi-layer modified silicide-based high-temperature oxidation-resistant coating
CN118207607A